Instrumen Penilaian Derajat Kecanggihan pada Sistem E-Learning Pendidikan Menengah Atas - Lumbangaol, Anita Febriany; Panjaitan, Santi; Julianti, Metiovani; Sitorus, Felix Arnes; Rahayu, Oky; Hutauruk, Joshua Partogi; Simanjuntak, Indah Debora Salmanita; Tiara, Karen; Manik, Yosef Barita Sar (JOEAI (Journal of Education and Instruction), 2022)
This study aims to determine whether the implementation of e-learning at the secondary education level has met the standards needed by students in developing their potential by formulating criteria and indicators for evaluating technology or e-learning with technometric methodologies. Data collection methods consist of observations, interviews, Focus Group Discussions (FGD) and literature studies and data processing is carried out using a technometric methodology consisting of Technoware, Humanware, Infoware, and Orgaware (THIO) components. The results of the study, it was found that in the instrument of degree of sophistication in high school level e-learning (SMA) there are components of supporting technology in e-learning including technoware, humanware, infoware and orgaware which consists of criteria, sub-criteria, and sub-criteria. In conclusion, the e-learning process at the secondary education level has met the standards needed by students in developing their potential, with the existence of technological components that support e-learning learning. Keywords: e-learning, senior high school, technometric, technoware, humanware, infoware dan orgaware